The Impact of Patient Deaths on General Surgeons’ Psychosocial Well-Being and Surgical Practices - Akyol, Cihangir; Celik, Suleyman Utku; Koc, Mehmet Ali; Bayindir, Duygu Sezen; Gocer, Mehmet Ali; Karakurt, Buket; Kaya, Mustafa; Kekec, Sena Nur; Simsek, Furkan Aydin (Frontiers in Surgery, 2022)
Background: Patient deaths are an unavoidable occurrence in surgical practice. Although these events have negative effects on patients and their families, they can also have a profound adverse impact on surgeons who are unprepared for these deep emotional experiences. This study aims to investigate the impact of patient deaths on general surgeons’ psychosocial well-being and surgical practices. Methods: A national cross-sectional survey of a 30-item questionnaire was conducted. The survey evaluated the surgeons’ demographics, professional and practice characteristics, and the impact of patient deaths on their emotional well-being, professional career, and social life. Results: Four hundred eighty participants completed the survey. One-third of the participants reported that patient deaths affected their emotional well-being, 23.3% reported that patient deaths affected their social life, and 34.2% reported that patient deaths affected their professional career. Surgeons who reported suffering from the emotional impact of death exhibited no differences in terms of place of practice, academic title, surgical experience, work hours, or annual surgical volume. Middle-aged surgeons (p = 0.004), females (p = 0.041), and surgeons who reported feeling burned out (p < 0.001) were more likely to be affected by patient loss. Feelings of sadness, worry, and stress were most reported. A total of 18.1% of the participants indicated that they considered taking a break after patient death, and 11.9% thought they would abandon their surgical career. Conclusions: The findings of this study suggest that patient death affects surgeons’ psychosocial well-being and surgical practices. Greater awareness and effort are required at the personal, institutional, and organizational level to provide effective support, helping surgeons to cope with the emotional burden of patient deaths.